PENCIPTAAN KARYA TARI â€œANAKKU BERMAINâ€ - Silvi Fitriah Diana (Institut Seni Indonesia Surakarta, 2014)
The reason for this research was the lack of development of creativity and the poor learningspirit among school children. This is due to the fact that educators still tend to use conventionalteaching methods in the teaching and learning process. The question addressed in the research iswhether the creativity and learning spirit of children in the first and second years of the An-NurKindergarten in the District of Jember, in which a play-based learning model is implemented,will develop to an optimal level. The goal of this research is to discover the results of implementinga play-based learning model on the creativity and learning spirit of children at school. Thebenefits of the research are: (1) for the children, to increase their learning spirit and develop theircreativity; (2) for the educator, to implement play-based learning in the teaching and learningprocess in the classroom; and (3) for the school, to create an innovation in the learning processwhich is suitable for the world of children while at the same time remaining relevant to thenuance of learning that is required according to the curriculum. The nature of the research is aclassroom action study which includes planning, implementation, and evaluation. The researchdata includes the data of the activities and the results of the development of the childrenâ€™s creativitywith the implementation of a play-based learning model. The data was obtained throughÂ demonstrations, observation, discussions, and field notes. The results of the research show thatthere is an increase in learning, evident both in the activities of the teachers in the teaching andlearning process and also in the results of the observation and demonstrations. This increase canbe seen in every study inside the classroom which uses personal notes, firstly with adequate development(c) and secondly with very good development (SB). The conclusions of the research arethat using a play-based learning model can increase the creativity and learning spirit of childrenin the An-Nur Kindergarten in the Sub-District of Kaliwates in the District of Jember.Keywords: Play-Based Learning Model, Creativity, Childrenâ€™s Learning SpiritÂ